The Effect of Biochar on the Changes of Some Soil Bacterial Groups and the Development of Green Peas - in Vitro Model Experiment - Kókai, Anett; Haider, Ali; Haythem, Saadi; Biró, Borbála; Ringer, Mariann; Kocsis, Tamás (Journal of Central European Green Innovation, 2022)
One of the major challenges of our world is the continuous decreasing soil productivity. The decreasing crop averages due to natural and anthropogenic processes necessitate the application of new agrotechnical technologies and methods. Biochar, which can be produced by the pyrolysis decomposition of organic materials, is one of the tools used worldwide to improve the water and nutrient retention capacity of soils. During the pyrolysis, the carbon content of the biomass-based raw material turns into aromatic carbon groups, and amorphous and graphitic structures, which is called biochar. Our aim was to investigate the effect of plant coal biochar on the microbiological activity- and diversity of low-humus sandy soil and on the growth of green peas (Pisum sativum L.) in an in vitro experiment. In the nine-week pot experiment, four parallel measurements were set up on increasing biochar doses (expressed in m m%) to determine the optimal concentration. The amount of bacteria that could be cultivated from the soil and the proportion of each biochemical group were examined once per week. At the end of the experiment, the mass of the biomass of the test plant (shoot + root) was determined, as well as the number of the root nodules, which change as a result of the treatments. Based on our results, some rapid biochemistry tests (catalase and oxidase) combined with the micromorphological characteristics of the cells may be suitable for detecting changes in the soil microbiome. In the examined soil, when determining the optimal amount/treatment of biochar, take attention to the different environmental needs of the plant and the microbes, since the optimum of plant biomass production did not completely overlap with the number of nitrogen-fixing root nodules.